Iridium-cluster-loaded strontium titanate as well as preparation method and application thereof
By loading strontium titanate with iridium clusters, the energy barrier of the oxygen evolution reaction is reduced by using the Ti-O-Ir interface, which solves the problems of high cost of existing iridium-based oxide catalysts and difficult to take into account both activity and stability, and achieves efficient and long-term stable electrocatalytic performance, and reduces the catalyst cost.
Patent Information
- Application Number
- CN202411793485.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The iridium-based oxide catalysts used in existing proton exchange membrane water electrolytic cells (PEMWEs) have problems such as high cost and difficulty in taking into account both electrocatalytic activity and stability, which leads to their lack of competitiveness in the market.
By loading iridium cluster strontium titanate (IrO2-y@SrTiO3-x), the material generates an in-situ reconstructed Ti-O-Ir interface through bias-induced Ti leaching, significantly reducing the energy barrier of the oxygen evolution reaction and improving electrocatalytic activity and cycling stability.
The strontium titanate loaded with iridium clusters can operate efficiently and stably for more than 800 hours under the operating conditions of PEMWE, which far exceeds the performance and maximum operating time of commercial catalysts. At the same time, it significantly reduces the content of precious metal Ir in the catalyst and reduces costs.
Smart Images

Figure CN119506946A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to strontium titanate loaded with iridium clusters, and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane water electrolyzer (PEMWE) has the advantages of high operating current density, high hydrogen purity and low resistance loss, making it the preferred technology for high efficiency and small footprint. However, the strong acidity and oxidizing environment under PEMWE working conditions pose great challenges to catalyst activity and stability. Due to the high overpotential of the oxygen evolution reaction (OER), PEMWE has high requirements for anode electrocatalysts. To date, the most widely used OER catalyst in PEMWE technology is iridium-based oxide. However, iridium-based oxide not only has the problem of high cost due to the high loading of precious metal iridium, but also cannot balance electrocatalytic activity and stability, making PEMWE equipment relying on iridium-based oxide not competitive in the market. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide a strontium titanate loaded with iridium clusters and a preparation method and application thereof. The strontium titanate loaded with iridium clusters not only has excellent electrocatalytic activity, but also has long-term stability, and can operate efficiently and stably for a long time under the working conditions of PEMWE.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] The present invention provides a strontium titanate loaded with iridium clusters, comprising: strontium titanate and an iridium cluster loaded on the surface of the strontium titanate; the components of the iridium cluster include iridium element and iridium oxide wrapped on the surface of the iridium element; the chemical composition of the strontium titanate is SrTiO 3-x , 0<x<0.5; the chemical composition of the iridium oxide is IrO 2-y , 0<y<2; the strontium carbonate has a cubic octahedral structure.
[0006] Preferably, the diameter of the strontium titanate loaded with iridium clusters is 150-300 nm.
[0007] Preferably, the mass percentage of iridium element in the strontium titanate loaded with iridium clusters is 1 to 60%.
[0008] The present invention also provides a method for preparing strontium titanate loaded with iridium clusters according to the above technical solution, comprising the following steps:
[0009] Cubooctahedral SrTiO3, a compound containing iridium ions, an alkali source, a reducing alcohol and water are mixed and subjected to a hydrothermal reaction to obtain strontium titanate loaded with iridium clusters.
[0010] Preferably, the compound containing iridium ions includes one or more of iridium chloroacid, iridium tetrachloride and potassium hexachloroiridate (IV).
[0011] Preferably, the alkali source is an alkali metal hydroxide; the alkali metal hydroxide includes one or more of potassium hydroxide, lithium hydroxide, cesium hydroxide and sodium hydroxide.
[0012] Preferably, the reducing alcohol comprises ethylene glycol and / or glycerol.
[0013] Preferably, the temperature of the hydrothermal reaction is 160-220° C.; the time of the hydrothermal reaction is 12-36 hours.
[0014] The present invention also provides the use of the strontium titanate loaded with iridium clusters described in the above technical solution or the strontium titanate loaded with iridium clusters prepared by the preparation method described in the above technical solution as an anode electrocatalyst in a proton exchange membrane water electrolyzer.
[0015] The present invention also provides an anode of a proton exchange membrane water electrolyzer, comprising an anode substrate and an anode electrocatalyst coated on the surface of the anode substrate;
[0016] The anode electrocatalyst is the strontium titanate loaded with iridium clusters described in the above technical solution or the strontium titanate loaded with iridium clusters prepared by the preparation method described in the above technical solution.
[0017] The present invention provides a strontium titanate loaded with iridium clusters, comprising: strontium titanate and an iridium cluster loaded on the surface of the strontium titanate; the components of the iridium cluster include iridium element and iridium oxide wrapped on the surface of the iridium element; the chemical composition of the strontium titanate is SrTiO 3-x , 0<x<0.5; the chemical composition of the iridium oxide is IrO 2-y, 0<y<2; the strontium carbonate has a cubic octahedral structure. In the electrocatalytic oxygen evolution reaction, after applying voltage, the strontium titanate loaded with iridium clusters provided by the present invention can generate an in-situ reconstructed Ti-O-Ir interface through bias-induced Ti leaching, and the strontium titanate with a cubic octahedral structure is more likely to expose the 110 crystal plane and form a Ti-O-Ir interface with the iridium cluster. This Ti-O-Ir interface stabilizes the structure of the strontium titanate loaded with iridium clusters, and can significantly reduce the energy barrier of the oxygen evolution reaction, reduce the overpotential, greatly improve the activity of the oxygen evolution reaction, and significantly improve the electrocatalytic activity and cycle stability of the strontium titanate loaded with iridium clusters; moreover, when a voltage is applied, the SrTiO3 carrier induces Sr leaching to trigger the formation of OH mediated by the carrier lattice oxygen, resulting in the enrichment of OH at the Ti-O-Ir interface, which is conducive to OH overflow. This reverse OH lattice overflow-assisted AEM (adsorption oxidation mechanism of metal as redox center when the electronic state near the Fermi level is metal) reaction pathway can circumvent the traditional linear scaling relationship, thereby reducing the reaction energy barrier and improving the electrocatalytic activity of strontium titanate loaded with iridium clusters. In addition, the Ti-O-Ir interface also ensures the stability of iridium oxide even at challenging high potentials by effectively keeping the Ir position in a lower redox state. The strontium titanate loaded with iridium clusters provided by the present invention can be used as a catalyst to operate stably for more than 800 hours under the operating conditions of a proton exchange membrane water electrolyzer (PEMWE), far exceeding the performance and maximum operating time of commercial catalysts.
[0018] In addition, the present invention uses strontium titanate as the base material and loads iridium clusters, which can significantly reduce the content of precious metal Ir in the catalyst and greatly reduce the cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the XRD characterization diagram of the strontium titanate loaded with iridium clusters prepared in Example 2;
[0020] Figure 2 The strontium titanate material (SrTiO 3-x ) and the OER polarization curves of the commercial catalyst IrO2 (C-IrO2) in Comparative Example 2;
[0021] Figure 3 The strontium titanate material (SrTiO 3-x )’s OER polarization curve;
[0022] Figure 4 It is a polarization curve diagram of a proton exchange membrane water electrolyzer (PEMWE) using the commercial catalyst IrO2 (Com-IrO2) in Comparative Example 2 as an anode electrocatalyst;
[0023] Figure 5 is a polarization curve diagram of a proton exchange membrane water electrolyzer (PEMWE) using strontium titanate loaded with iridium clusters prepared in Example 2 as an anode electrocatalyst;
[0024] Figure 6 The iridium cluster-loaded strontium titanate prepared in Example 2 is 1A·cm -2 And constant current test results at 80℃. DETAILED DESCRIPTION
[0025] The present invention provides a strontium titanate loaded with iridium clusters, comprising: strontium titanate and an iridium cluster loaded on the surface of the strontium titanate; the components of the iridium cluster include iridium element and iridium oxide wrapped on the surface of the iridium element; the chemical composition of the strontium titanate is SrTiO 3-x , 0<x<0.5; the chemical composition of the iridium oxide is IrO 2-y , 0<y<2; the strontium carbonate has a cubic octahedral structure.
[0026] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0027] The strontium titanate loaded with iridium clusters provided by the present invention comprises: strontium titanate; the chemical composition of the strontium titanate is SrTiO 3-x , 0<x<0.5.
[0028] As an embodiment, 0<x<0.3, in a specific embodiment, the chemical composition of the strontium titanate is SrTiO 2.72 ; The strontium titanate has a cubic octahedral structure.
[0029] The strontium titanate loaded with iridium clusters provided by the present invention comprises: an iridium cluster loaded on the surface of the strontium titanate; the components of the iridium clusters include iridium element and iridium oxide wrapped on the surface of the iridium element; the chemical composition of the iridium oxide is IrO 2-y , 0<y<2.
[0030] As an embodiment, the diameter of the strontium titanate loaded with iridium clusters is 150-300 nm, and in a specific embodiment, it is 200-250 nm; the mass percentage of iridium element in the strontium titanate loaded with iridium clusters is 1-60%, and in a specific embodiment, it is 30-41.83%.
[0031] In the electrocatalytic oxygen evolution reaction, after applying voltage, the strontium titanate loaded with iridium clusters provided by the present invention can generate an in-situ reconstructed Ti-O-Ir interface through bias-induced Ti leaching, and the strontium titanate with a cubic octahedral structure is more likely to expose the 110 crystal plane and form a Ti-O-Ir interface with the iridium cluster. This Ti-O-Ir interface stabilizes the structure of the strontium titanate loaded with iridium clusters, and can significantly reduce the energy barrier of the oxygen evolution reaction, reduce the overpotential, greatly improve the activity of the oxygen evolution reaction, and significantly improve the electrocatalytic activity and cycle stability of the strontium titanate loaded with iridium clusters; moreover, when a voltage is applied, the SrTiO3 carrier induces Sr leaching to trigger the formation of OH mediated by the carrier lattice oxygen, resulting in the enrichment of OH at the Ti-O-Ir interface, which is conducive to OH overflow. This reverse OH lattice overflow-assisted AEM (adsorption oxidation mechanism of metal as redox center when the electronic state near the Fermi level is metal) reaction pathway can circumvent the traditional linear scaling relationship, thereby reducing the reaction energy barrier and improving the electrocatalytic activity of strontium titanate loaded with iridium clusters. In addition, the Ti-O-Ir interface also ensures the stability of iridium oxide even at challenging high potentials by effectively keeping the Ir position in a lower redox state. The strontium titanate loaded with iridium clusters provided by the present invention can be used as a catalyst to operate stably for more than 800 hours under the operating conditions of a proton exchange membrane water electrolyzer (PEMWE), far exceeding the performance and maximum operating time of commercial catalysts.
[0032] The present invention also provides a method for preparing strontium titanate loaded with iridium clusters according to the above technical solution, comprising the following steps:
[0033] Cubooctahedral SrTiO3, a compound containing iridium ions, an alkali source, a reducing alcohol and water are mixed and subjected to a hydrothermal reaction to obtain strontium titanate loaded with iridium clusters.
[0034] As an embodiment, the preparation method of the cubic octahedral SrTiO3 comprises the following steps:
[0035] Mixing a titanium-containing compound, a first alkali source, a first reducing alcohol, a first strontium salt and water, and performing a first hydrothermal reaction to obtain a SrTiO3 precursor;
[0036] The SrTiO3 precursor, aluminum salt and water are mixed and dried, and then the obtained mixture is mixed with a second strontium salt and calcined to obtain cubic octahedral SrTiO3.
[0037] The present invention mixes a titanium-containing compound, a first alkali source, a first reducing alcohol, a first strontium salt and water, and performs a first hydrothermal reaction to obtain a SrTiO3 precursor.
[0038] As an embodiment, the titanium-containing compound includes titanium trichloride and / or titanium dioxide, and in a specific embodiment, it is titanium trichloride. In an embodiment of the present invention, the titanium-containing compound is a TiCl3 solution; the TiCl3 solution is prepared by dissolving TiCl3 in 30wt% HCl, and the mass concentration of TiCl3 in the TiCl3 solution is 15-20%, and in a specific embodiment, it is 20%.
[0039] As an embodiment, the first alkali source is an alkali metal hydroxide; the alkali metal hydroxide includes one or more of potassium hydroxide, lithium hydroxide, cesium hydroxide and sodium hydroxide, and in specific embodiments, it is potassium hydroxide, lithium hydroxide, cesium hydroxide or sodium hydroxide; the mass ratio of the titanium-containing compound to the first alkali source is 0.01 to 2:1, and in specific embodiments, it is 0.05:1.
[0040] As an embodiment, the first reducing alcohol includes ethylene glycol and / or propylene glycol, and in a specific embodiment, it is ethylene glycol; the water is ultrapure water; the mass ratio of the water to the first reducing alcohol is 20 to 100:1, and in a specific embodiment, it is 55:1.
[0041] As an embodiment, the first strontium salt is strontium chloride, and in a specific embodiment, it is strontium chloride hexahydrate; the mass ratio of water to the first strontium salt is 20-100:1, and in a specific embodiment, it is 55:0.74.
[0042] As an implementation mode, the mass ratio of the first alkali source to water is 1:10-100, and in a specific embodiment is 4:55.
[0043] As an embodiment, the titanium-containing compound, the first alkaline source, the first reducing alcohol, the first strontium salt and water are mixed as follows: the titanium-containing compound is added to the water containing the first reducing alcohol, a first stirring is performed, then an aqueous solution of the first alkaline source is added, a second stirring is performed, and finally a strontium salt is added for a third stirring; the first stirring, the second stirring and the third stirring rate are independently 1000 rpm; the first stirring, the second stirring and the third stirring time are independently 5 to 20 minutes, and in a specific embodiment, 5 to 15 minutes. The present invention does not specifically limit the rates of the first stirring, the second stirring and the third stirring, as long as they can be stirred evenly.
[0044] As an embodiment, the temperature of the first hydrothermal reaction is 160-220°C, and in a specific embodiment, it is 180-200°C; the time of the first hydrothermal reaction is 1-48h, and in a specific embodiment, it is 2-24h; the equipment used for the first hydrothermal reaction is a stainless steel autoclave lined with polytetrafluoroethylene.
[0045] As an embodiment, after the first hydrothermal reaction, the product of the first hydrothermal reaction is cooled, solid-liquid separation is performed, and the obtained solid is washed and dried to obtain a SrTiO3 precursor.
[0046] As an embodiment, the cooling is cooling by immersing in ice water; the cooling is to room temperature; the solid-liquid separation is centrifugation; the speed of the centrifugation is 5000-11000rpm, 8000-10000rpm in the specific embodiment, the time is 3-10min, 5min in the specific embodiment; the washing is sequentially washing with water and washing with alcohol; the reagent used for the water washing is ultrapure water; the reagent used for the alcohol washing is ethanol; the washing is until the upper clear liquid is clarified; the drying temperature is 60-80℃, 60-70℃ in the specific embodiment; the drying is vacuum drying; the vacuum degree of the vacuum drying is -0.1MPa. The present invention has no specific requirements for the drying time, and complete drying is sufficient. In an embodiment of the present invention, the vacuum drying time is 12h.
[0047] After obtaining the SrTiO3 precursor, the present invention mixes the SrTiO3 precursor, aluminum salt and water, and after drying, mixes the obtained mixture with a second strontium salt and calcines to obtain cubic octahedral SrTiO3.
[0048] As an embodiment, the aluminum salt is aluminum chloride, and in a specific embodiment, it is AlCl3·6H2O; the molar ratio of Ti in the SrTiO3 precursor to Al in the aluminum salt is 1:0.004-0.02, and in a specific embodiment, it is 1:0.004. Aluminum salt, as a template, can precisely and controllably adjust the percentage of {110} faces on the crystal surface.
[0049] As an embodiment, the second strontium salt is strontium chloride, and in a specific embodiment, it is strontium chloride hexahydrate; the molar ratio of Sr in the SrTiO3 precursor to Sr in the second strontium salt is 1:8-10, and in a specific embodiment, it is 1:10.
[0050] As an embodiment, the SrTiO3 precursor, aluminum salt and water are mixed as follows: the SrTiO3 precursor and aluminum salt are dispersed in water; the dispersion is carried out under stirring; the stirring rate is 1000rpm; the present invention has no specific requirements for the stirring rate and time, as long as it can be stirred evenly.
[0051] As an implementation mode, the ratio of the total mass of the SrTiO3 precursor and the aluminum salt to the mass of water is 0.04-0.25:1, and in a specific embodiment is 0.16:1.
[0052] As an embodiment, the drying temperature is 80-150°C, and in a specific embodiment, 100-120°C; the drying is carried out under stirring. The present invention has no special restrictions on the stirring rate and drying time, as long as it can be completely dried. In an embodiment of the present invention, the stirring rate is 1000rpm.
[0053] As an embodiment, the calcination temperature is 750-1250°C, and in a specific embodiment, it is 1000-1150°C; the calcination holding time is 8-12h, and in a specific embodiment, it is 9-10h; the heating rate from room temperature to the calcination temperature is 3-5°C / min, and in a specific embodiment, it is 4°C / min; the calcination is carried out in air.
[0054] As an embodiment, after the calcination, the method further comprises: cooling the calcined product from the calcination temperature to room temperature, washing and drying in sequence; the cooling rate is 2-3°C / min, and in a specific embodiment, it is 2.5°C / min; the reagent used for the washing is water, and in a specific embodiment, it is ultrapure water; the number of washings is 2-5 times, and in a specific embodiment, it is 3-4 times; the washing is centrifugal washing; the speed of the centrifugal washing is 5000-10000rpm, and in a specific embodiment, it is 8000-10000rpm; the time of each centrifugal washing is 3-10min, and in a specific embodiment, it is 5min; the drying temperature is 60-80°C, and in a specific embodiment, it is 60°C; the present invention has no specific requirements for the drying time, and complete drying is sufficient; the drying is vacuum drying; the vacuum degree of the vacuum drying is -0.1MPa. In an embodiment of the present invention, the drying time is 12h.
[0055] As an embodiment, the iridium ion-containing compound includes one or more of iridium chloroacid, iridium tetrachloride and potassium hexachloroiridate (IV), and in a specific embodiment, it is iridium chloroacid; the molar ratio of Ir in the iridium ion-containing compound to Sr in cubic octahedral SrTiO3 is 1 to 2:1 to 8, and in a specific embodiment, it is 2:1, 1:1, 1:2, 1:4 or 1:8.
[0056] As an embodiment, the alkali source is an alkali metal hydroxide; the alkali metal hydroxide includes one or more of potassium hydroxide, lithium hydroxide, cesium hydroxide and sodium hydroxide, and in a specific embodiment, it is potassium hydroxide; the mass ratio of the iridium ion-containing compound to the alkali source is 1.5 to 20:1, and in a specific embodiment, it is 2 to 16:1.
[0057] As an embodiment, the reducing alcohol includes ethylene glycol and / or glycerol, and in a specific embodiment, it is ethanol; the mass ratio of the iridium ion-containing compound to the reducing alcohol is 0.00047 to 0.03:1, and in a specific embodiment, it is 0.0034 to 0.029:1.
[0058] As an embodiment, the mass ratio of the compound containing iridium ions to water is 1:50-650, and in a specific embodiment, it is 1:75-625.
[0059] As an embodiment, cuboctahedral SrTiO3, a compound containing iridium ions, an alkali source, a reducing alcohol and water are mixed as follows: cuboctahedral SrTiO3 and a compound containing iridium ions are dispersed in water, an alkali source is added to the obtained dispersion for a first stirring, and a reducing alcohol is added for a second stirring; the first stirring and the second stirring rates of the present invention have no specific requirements, and the stirring is uniform; the time of the first stirring and the second stirring is independently 5 to 40 minutes, and in a specific embodiment, it is 5 to 30 minutes. In an embodiment of the present invention, the rates of the first stirring and the second stirring are 1000rpm.
[0060] As an embodiment, the temperature of the hydrothermal reaction is 160-220°C, and in a specific embodiment, it is 180-200°C; the time of the hydrothermal reaction is 12-36h, and in a specific embodiment, it is 18-24h; the equipment used for the hydrothermal reaction is a stainless steel autoclave lined with polytetrafluoroethylene.
[0061] As an embodiment, after the hydrothermal reaction, it also includes: cooling the product of the hydrothermal reaction to room temperature and then washing; the washing is sequentially performing water washing and alcohol washing; the number of water washings is 2 to 5 times, and in a specific embodiment, it is 2 to 4 times; the number of alcohol washings is 2 to 5 times, and in a specific embodiment, it is 2 to 4 times; the reagent used for the water washing is ultrapure water; the reagent used for the alcohol washing is ethanol; the washing is centrifugal washing; the rotation speed of each centrifugal washing is 5000 to 11000 rpm, and in a specific embodiment, it is 8000 to 10000 rpm; the time of each centrifugal washing is 3 to 10 minutes, and in a specific embodiment, it is 5 to 8 minutes.
[0062] The present invention also provides the use of the strontium titanate loaded with iridium clusters described in the above technical solution or the strontium titanate loaded with iridium clusters prepared by the preparation method described in the above technical solution as an anode electrocatalyst in a proton exchange membrane water electrolyzer.
[0063] As an implementation mode, the application is: producing hydrogen by electrolyzing water.
[0064] The present invention also provides an anode of a proton exchange membrane water electrolyzer, comprising an anode substrate and an anode electrocatalyst coated on the surface of the anode substrate;
[0065] The anode electrocatalyst is the strontium titanate loaded with iridium clusters described in the above technical solution or the strontium titanate loaded with iridium clusters prepared by the preparation method described in the above technical solution.
[0066] As an embodiment, the method for preparing the anode of the proton exchange membrane water electrolyzer comprises the following steps: coating strontium titanate loaded with iridium clusters on the surface of the anode substrate; the anode substrate is a Nafion 115 proton exchange membrane; the coating is spraying; the present invention has no special limitation on the thickness of the coating, and the spraying can be uniform.
[0067] The iridium cluster-loaded strontium titanate provided by the present invention can be used as a catalyst to operate stably and efficiently for more than 800 hours under the operating conditions of a proton exchange membrane water electrolyzer (PEMWE), far exceeding the performance and maximum operating time of commercial catalysts.
[0068] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0069] All chemicals were obtained from commercial suppliers of analytical grade and used as received without further purification. Iridochloric acid (H2IrCl6), ethylene glycol (EG), potassium hydroxide (KOH), titanium chloride solution (TiCl3), strontium chloride hexahydrate (SrCl2·6H2O), aluminum chloride hexahydrate (AlCl3·6H2O), and lithium hydroxide monohydrate (LiOH·H2O) were purchased from Aladdin.
[0070] Example 1
[0071] (1) Synthesis of SrTiO3 precursor: 0.8 mL of 20 wt% TiCl3 solution (TiCl3 dissolved in 30 wt% HCl) was added to 25 mL of ultrapure water containing 0.9 mL of ethylene glycol cooled in an ice bath and stirred at 1000 rpm for 5 min. Then, 30 mL of LiOH aqueous solution containing 4.0 g of LiOH·H2O was added and stirred at 1000 rpm for 15 min. Then, 0.74 g of SrCl2·6H2O was stirred at 1000 rpm for 10 min, and then the mixed raw materials were transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene, and the first hydrothermal reaction was carried out at 180°C for 2 h. After the reaction, the autoclave was directly immersed in ice water and quickly cooled to room temperature, and the precipitate was recovered by centrifugation at 10000 rpm for 5 min, and then washed with ultrapure water and ethanol until the supernatant was clear, and then vacuum dried at 60°C and a vacuum degree of -0.1 MPa for 12 h to obtain a SrTiO3 precursor;
[0072] (2) Synthesis of cubic octahedral SrTiO3 in SrCl2·6H2O molten salt: The above SrTiO3 precursor and AlCl3·6H2O were mixed at a molar ratio of 1:0.004 (Ti / Al molar ratio) and dispersed in 20 mL of ultrapure water at 1000 rpm. The mixture was evaporated in an evaporating dish at 120°C at 1000 rpm until completely dry. The resulting mixture was collected and mixed with SrCl2·6H2O. The S in the SrTiO3 precursor was The molar ratio of r and Sr in SrCl2·6H2O is 1:10, and then an alumina crucible is used to heat the mixture from room temperature to 1150°C at 4°C / min in air and calcine for 10 hours, and then cooled to room temperature at 2.5°C / min, and then centrifuged and washed three times with ultrapure water at a speed of 10000rpm and a centrifugal time of 5 minutes each, and then dried at 60°C for 12 hours in a vacuum drying chamber with a vacuum degree of -0.1MPa to obtain cubic octahedral SrTiO3.
[0073] Example 2
[0074] First, 80.06 mg H2IrCl6 and 18.04 mg of cuboctahedral SrTiO3 prepared in Example 1 were dispersed in 25 mL of water, the molar ratio of Ir in H2IrCl6 to Sr in cuboctahedral SrTiO3 being 2:1. 20 mg of KOH was added to the dispersion, and the mixture was stirred at 1000 rpm for 5 min. Then, 10 mL of ethylene glycol (1.1135 g / cm 3 , 20°C), stirred at 1000 rpm for 30 min, the obtained mixed solution was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene, and hydrothermally reacted at 180°C for 24 h. After cooling to room temperature, it was centrifugally washed twice with water and ethanol in sequence, with the speed of each centrifugal washing being 10000 rpm and the time of each centrifugal washing being 5 min, to obtain strontium titanate (IrO 2-y @SrTiO 3-x (2:1), where SrTiO 2.72 , 0<y<2, diameter is 200nm, iridium element accounts for 41.83%).
[0075] Example 3
[0076] The difference from Example 2 is that the molar ratio of Ir in H2IrCl6 to Sr in cubic octahedral SrTiO3 is 1:1, and the strontium titanate (IrO 2-y @SrTiO 3-x (1:1)).
[0077] Example 4
[0078] The difference from Example 2 is that the molar ratio of Ir in H2IrCl6 to Sr in cubic octahedral SrTiO3 is 1:2, and the strontium titanate (IrO 2-y @SrTiO 3-x (1:2)).
[0079] Example 5
[0080] The difference from Example 2 is that the molar ratio of Ir in H2IrCl6 to Sr in cubic octahedral SrTiO3 is 1:4, and the strontium titanate (IrO 2-y @SrTiO 3-x (1:4)).
[0081] Example 6
[0082] The difference from Example 2 is that the molar ratio of Ir in H2IrCl6 to Sr in cubic octahedral SrTiO3 is 1:8, and the strontium titanate (IrO 2-y @SrTiO 3-x (1:8)).
[0083] Comparative Example 1
[0084] The difference from Example 2 is that in Example 2, IrO 2-y @SrTiO 3-x During the process, H2IrCl6 was removed and a hydrothermal reaction was performed to obtain strontium titanate material (SrTiO 3-x ).
[0085] Comparative Example 2
[0086] A commercial catalyst IrO2 (C-IrO2) was used as a comparative example.
[0087] Application Example 1
[0088] The strontium titanate loaded with iridium clusters prepared in Example 2 was sprayed on the surface of the anode substrate (Nafion 115 proton exchange membrane) of a proton exchange membrane water electrolyzer to electrolyze water to produce hydrogen.
[0089] Application Examples 2 to 5
[0090] The difference from Application Example 1 is that the strontium titanate loaded with iridium clusters prepared in Example 2 is replaced by the strontium titanate loaded with iridium clusters prepared in Examples 3 to 6 respectively.
[0091] Comparative application example 1
[0092] The difference from Application Example 1 is that the strontium titanate loaded with iridium clusters prepared in Example 2 is replaced by the strontium titanate material (SrTiO 3-x ).
[0093] Comparative Application Example 2
[0094] The difference from Application Example 1 is that the strontium titanate loaded with iridium clusters prepared in Example 2 is replaced by the commercial catalyst IrO2 (C-IrO2) of Comparative Example 2.
[0095] Performance Testing
[0096] (1) Figure 1 This is the XRD characterization diagram of the strontium titanate loaded with iridium clusters prepared in Example 2.
[0097] from Figure 1 It can be seen that the iridium clusters are loaded on the strontium titanate carrier. The strontium titanate loaded with iridium clusters prepared by the present invention is different from SrTiO in XRD characterization. 2.72 The peak shape is consistent.
[0098] (2) Figure 2 The strontium titanate material (SrTiO 3-x ) and the OER polarization curves of the commercial catalyst IrO2 (C-IrO2) in Comparative Example 2.
[0099] from Figure 2 It can be seen that IrO 2-y @SrTiO 3-x The performance of (2:1) is the best at 10 mA cm -2 The overpotential is only 202 mV at a current density of 1.3 Å, which is a significant advantage compared to commercial catalysts.
[0100] (3) Figure 3 The strontium titanate material (SrTiO 3-x )’s OER polarization curve.
[0101] from Figure 3 It can be seen that pure SrTiO 3-x The carrier does not have OER activity.
[0102] (4) Figure 4 This is a polarization curve diagram of a proton exchange membrane water electrolyzer (PEMWE) using the commercial catalyst IrO2 (Com-IrO2) in Comparative Example 2 as the anode electrocatalyst.
[0103] Depend on Figure 4 It can be seen that under the working conditions of PEMWE (80℃), the commercial catalyst IrO2 (Com-IrO2) reaches 2A·cm -2 The current density needs to be 1.97V to reach 1A·cm -2The current density needs to be 1.77V.
[0104] (5) Figure 5 This is a polarization curve diagram of a proton exchange membrane water electrolyzer (PEMWE) using the iridium cluster-loaded strontium titanate prepared in Example 2 as an anode electrocatalyst.
[0105] Depend on Figure 5 It can be seen that the strontium titanate loaded with iridium clusters reaches 2A·cm under the working conditions of PEMWE (80℃). -2 The current density only needs 1.854V to reach 1A·cm -2 The current density only needs to be 1.662 V. Strontium titanate loaded with iridium clusters has a significant advantage over commercial catalyst IrO2 (Com-IrO2).
[0106] (6) Figure 6 The iridium cluster-loaded strontium titanate prepared in Example 2 is 1A·cm -2 And the constant current test results at 80℃.
[0107] Depend on Figure 6 It can be seen that strontium titanate loaded with iridium clusters can achieve 1A·cm -2 The catalyst can be stably operated for 800 h without obvious performance degradation, which is higher than most catalysts studied currently. This indicates that the strontium titanate loaded with iridium clusters prepared by the present invention has stable active metal Ir.
[0108] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A strontium titanate loaded with iridium clusters, characterized in that: include: Strontium titanate and an iridium cluster supported on the surface of the strontium titanate; the components of the iridium cluster include iridium element and iridium oxide wrapped on the surface of the iridium element; the chemical composition of the strontium titanate is SrTiO 3-x , 0<x<0.5; the chemical composition of the iridium oxide is IrO 2-y , 0<y<2; the strontium carbonate has a cubic octahedral structure.
2. The iridium cluster-loaded strontium titanate according to claim 1, characterized in that: The diameter of the strontium titanate loaded with iridium clusters is 150-300 nm.
3. The strontium titanate loaded with iridium clusters according to claim 1 or 2, characterized in that: The mass percentage of iridium element in the strontium titanate loaded with iridium clusters is 1-60%.
4. The method for preparing strontium titanate loaded with iridium clusters according to any one of claims 1 to 3, characterized in that: The following steps are involved: Cubooctahedral SrTiO3, a compound containing iridium ions, an alkali source, a reducing alcohol and water are mixed and subjected to a hydrothermal reaction to obtain strontium titanate loaded with iridium clusters.
5. The preparation method according to claim 4, characterized in that: The compound containing iridium ions includes one or more of iridium chloride, iridium tetrachloride and potassium hexachloroiridate (IV).
6. The preparation method according to claim 4, characterized in that: The alkali source is an alkali metal hydroxide; the alkali metal hydroxide includes one or more of potassium hydroxide, lithium hydroxide, cesium hydroxide and sodium hydroxide.
7. The preparation method according to claim 4, characterized in that: The reducing alcohol includes ethylene glycol and / or glycerol.
8. The preparation method according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 160-220° C.; the time of the hydrothermal reaction is 12-36 hours.
9. Use of the strontium titanate loaded with iridium clusters according to any one of claims 1 to 3 or the strontium titanate loaded with iridium clusters prepared by the preparation method according to any one of claims 4 to 8 as an anode electrocatalyst in a proton exchange membrane water electrolyzer.
10. An anode of a proton exchange membrane water electrolyzer, characterized in that: The invention comprises an anode substrate and an anode electrocatalyst coated on the surface of the anode substrate; The anode electrocatalyst is the strontium titanate loaded with iridium clusters as described in any one of claims 1 to 3 or the strontium titanate loaded with iridium clusters prepared by the preparation method as described in any one of claims 4 to 8.
Citation Information
Patent Citations
Perovskite supported cobalt efficient catalyst, preparation method and method for preparing methanol by partial oxidation of methane
CN113967476A
Iridium-containing microcrystalline nanometer material and preparation method and application thereof
CN119640325A
Field-effect superconducting transistor device
JP1991041783A
Cited By
Iridium-containing microcrystalline nanometer material and preparation method and application thereof
CN119640325A
Iridium-strontium titanate nano biocatalyst as well as preparation method and application thereof
CN121287744A
Ir-titanate nanobiocatalyst and preparation method and application thereof
CN121287744B